Language, music and computing : second International Workshop, LMAC 2017, St. Petersburg, Russia, April 17-19, 2017, Revised selected papers /: second International Workshop, LMAC 2017, St. Petersburg, Russia, April 17-19, 2017, Revised selected papers. (2019) - Unknown
No abstract available